VIDEO LECTURE AS A UNIVERSITY TEACHER’S SELF-REPRESENTATION IN THE CONDITIONS ELECTRONIC EDUCATIONAL RESOURCES IMPLEMENTATION - A. A. Kuznetsova; V. B. Nikishina (Высшее образование в России)
The problem of pedagogical self-presentation directly concerns teachers of various levels. It is especially important for teachers of medical higher education institutions. Video lecture as an educational product is a means of self-presentation of pedagogical activities, therefore, it can be a product of expert evaluation. All the components of pedagogical mastery are integrated in selfpresentation and create the whole teacher’s image, which helps him (her) to realize the pedagogical goals. Pedagogical interaction, influence, pedagogical communication, pedagogical skills cannot be manifested by a teacher without the skills of self-presentation, both in direct communication and while using of electronic educational resources, in particular video lectures. Professional video lecture is not a pure record of an academic lecture, it is a complicated technical and methodical product, and a teacher is not only a lecturer but also a pedagogical designer and strategist. Universal criteria for assessing video lecture are its external, communicative and content components. Additional components are the interactive effects of educational video lecture. Self-presentation of a teacher, no matter in direct communication or via an electronic resource, is akin to performance presenting the best patterns of pedagogical practice to students.